Criminal punishment of elderly defendants based on justice aspects - Hidayati, Raudhatul; Salsabila, Almas; Syahputra, Muhammad; Fadli, Sutia; Mareta, Anggun (Jurnal Geuthèë: Penelitian Multidisiplin, 2025)
The imposition of custodial sentences on elderly offenders contradicts the principles of justice, thus necessitating judicial discretion to ensure fair and humane sentencing. This study adopts a normative juridical approach, examining legal principles, norms, and doctrines as the basis for legal analysis. The findings indicate that imprisonment is inconsistent with the condition of elderly individuals, who are in the final stage of human development and often face deteriorating physical and psychological health. Such sanctions fail to align with the objectives of criminal punishment, which are not only retributive but also preventive. For elderly offenders particularly non recidivists the preventive function becomes less relevant. Accordingly, it is recommended that law enforcement officers, especially investigators, consider restorative justice as an alternative mechanism for dealing with elderly offenders, excluded from immoral and non-criminal crimes that are contrary to the public interest. Judges are also encouraged to impose probationary sentences on elderly offenders when the maximum penalty does not exceed one year and the individual is not a repeat recidivist.